Sistem Informasi Absensi Kepegawaian Berbasis WEB Pada PT. Prada Bangun Persada - Wibisono, Yusuf (Rifa'Institute, 2021)
PT. Prada Bangun Persada is a branch company that has a headoffice in the Jakarta area which is engaged in the field of SportsEquipment which has staff that must be managed properly. In thismanagement, the company makes an annual performance report,one of which contains a report on staffing. PT. Prada BangunPersada has several sections in the organizational structure, one ofwhich is the general responsibility section and the finance section.The general responsibility department and the finance department inthis company do not yet have an efficient personnel informationsystem application and are still processing data manually, resultingin various obstacles. Constraints experienced by the general personin charge are still using paper forms in making employee data andsubmitting employee letters so that they are less efficient and alwaysprovide paper forms. Then the storage of these letters still uses theirrespective folders based on the type of letter so that it is difficult toaccess and search for employee data and it is not safe if the storageis still using a folder and sometimes its validation is not handledproperly. Then in the finance department in the employee payrollprocess, which still calculates and saves with Microsoft excel formatfiles which causes low security and confidentiality of employeepayroll data at risk of file damage if exposed to a virus andemployees can easily access the file. This Personnel InformationSystem uses a 2-step method. First, the data collection method wascarried out in three ways, namely the observation method, theinterview method and the literature study. Second, the systemdevelopment method that will be used is the waterfall systemdevelopment method, and uses UML (Unified Modeling Language)notation as tools.